The Implications of Algorithmic Pricing for Coordinated Effects Analysis and Price Discrimination Markets in Antitrust Enforcement - Mcsweeny, Terrell; O'Dea, Brian (Antitrust, 2017)
[...]the Federal Trade Commission's authority under Section 5 of the FTC Act to prosecute "unfair methods of competition" may be the only current tool available to police individual instances of algorithmic collusion.23 Price Discrimination Markets To price discriminate successfully (i.e., charge different prices to different groups of consumers), firms must possess some degree of market power and there must be factors limiting the potential for buyers' arbitrage. [...]although it might sound odd from a market definition perspective, the agencies might appropriately define a price discrimination market for "politically liberal product consumers" and/or "politically conservative product consumers." [...]for 72 percent of consumers, it would be just that.50 Firm-wide diversion numbers in this example would likely obscure the competitive situation faced by specific demographic groups that might be subject to targeted price increases following a merger. [...]there would be little reason, ex ante, to suspect that the political views of consumers would be at all relevant in assessing competitive effects. [...]the size of specific price discrimination markets in which competitive concerns arise may be quite small compared to overall sales for a particular product. Both the government and the parties would need to devote more resources to such an investigation. [...]the fracturing of relevant product markets on the basis of price discrimination could increase the chances that a given merger will harm consumers in some relevant market.